Peranan Guru Agama Islam dalam Membelajarkan Siswa Menjadi Manusia yang Berakhlak Mulia - Umar, Jusnimar (Universitas Islam Negeri Raden Intan Lampung, 2016)
Al-Quran and al-ahadith reveal a lot about the personality of morality, both in the context of the vertical dimension of the relationship with Allah SWT. as well as horizontal relationships between men and their environment. As a matter of research, feedback main theories in both these sources is needed. That is why morality is defined into the operational level that can be observed from the symptoms appear.This study focused on the role of religious teachers of Islam in teaching students to become human morality in SMPN 29 Bandar Lampung, includes objectives to be achieved, the material presented, the role played and the methods used Islamic religious teachers, motivated students to become a man of morals noble, as well as changes in behavior and attitudes that result from learning morals in school, using a qualitative approach, in which the learning process and results are described, interpreted, and discussed to find the essence of meaning.The series of answers to the problems above, a finding which is very beneficial for Islamic religious teachers to understand, appreciate and carry out its function as educators so that the learning process morals students they can do in a situation education comprehensively in order to produce a human figure that is more potent noble.